Biomarkers of Pineal Region Tumors: A Review - Carr, Christopher (Ochsner J, 2019)
Background: The pineal gland, a small, pinecone-shaped organ deep within the brain, is responsible for producing melatonin. The gland consists of pineal parenchymal cells and glial cells that can form neoplasms. Pineal region neoplasms can also arise from germ cells and adjacent structures. This review focuses on detection of serum and cerebrospinal fluid (CSF) biomarkers of germ cell tumors and pineal parenchymal cell tumors, as these types comprise most neoplasms specific to the pineal region. Methods: For this review, we searched PubMed using the following keywords: biomarkers, germ cell tumor, germinoma, melatonin, pineal, pineal gland, pineal neoplasm, pinealoma, pineal parenchymal cell tumor, pineal region, and pineal tumor. We limited our search to full-text English articles and identified other relevant sources from the reference lists of identified articles. Results: Serum and CSF biomarker assays have a role in cases of suspected pineal germ cell or parenchymal neoplasms. Biomarkers including alpha-fetoprotein, beta-human chorionic gonadotropin, and placental alkaline phosphatase inform diagnosis and treatment and are important for monitoring germ cell tumor response to treatment. No biomarkers are currently available that inform diagnosis or treatment of pineal parenchymal tumors, although melatonin assays may have a role in monitoring response to treatment. Conclusion: Serum and CSF biomarkers in conjunction with clinical and radiographic evidence of a pineal region mass can inform the decision whether to undertake stereotactic biopsy or surgical excision or whether to proceed straight to medical treatment.